Enhanced Electrocaloric Effect and Energy Storage Density in Lead‐Free 0.8Na0.5Bi0.5TiO3‐0.2SrTiO3 Ceramics. Issue 4 (3rd January 2019) - Kumar, Ajit; Kumar, Raju; Singh, Kedar; Singh, Satyendra
Abstract : Enhanced electrocaloric response in lead‐free 0.8Na0.5 Bi0.5 TiO3 ‐0.2SrTiO3 (NBT‐0.2ST) ceramics are investigated using an indirect approach based on Maxwell's relations over a wide operating temperature range. The electrocaloric effect (ECE) is obtained over a broad temperature range with the maximum temperature change ( Δ T ) value reaching 0.75 K at the working temperature of 400 K under the electric field of 35 kV cm −1 . The maximum EC coefficient ( ζ = Δ T / Δ E ) is found to be 0.022 K·cm kV −1 at 400 K. Energy storage density of NBT‐0.2ST are calculated and found to be 0.36 J cm −3 at 393 K. High value of ECE and a wide working temperature range (350–450 K) make it a promising lead‐free ferroelectric material for applications in cooling technologies. Abstract : Electrocaloric response and energy storage density in lead‐free ferroelectric ceramic 0.8Na0.5 Bi0.5 TiO3 ‐0.2SrTiO3 (NBT‐0.2ST) synthesized by solid‐state method is investigated. Electrocaloric effect (Δ T ) is found to be 0.75 K at operating temperature 400 K under external field 35 kV cm −1 . Further, electrical energy storage density is calculated to be 0.36 J cm −3 . It is useful in solid‐state cooling, refrigeration, and energy storage devices.